The Inhibitory Effect of Alisol A 24-Acetate from Alisma canaliculatum on Osteoclastogenesis - Kwang-Jin Kim; Alain Simplice Leutou; Jeong-Tae Yeon; Sik-Won Choi; Seong Hwan Kim; Sung-Tae Yee; Kyung Hee Choi; Sang-Jip Nam; Young-Jin Son (International Journal of Endocrinology)
Osteoporosis is a disease that decreases bone mass. The number of patients with osteoporosis has been increasing, including an increase in patients with bone fractures, which lead to higher medical costs. Osteoporosis treatment is all-important in preventing bone loss. One strategy for osteoporosis treatment is to inhibit osteoclastogenesis. Osteoclasts are bone-resorbing multinucleated cells, and overactive osteoclasts and/or their increased number are observed in bone disorders including osteoporosis and rheumatoid arthritis. Bioactivity-guided fractionations led to the isolation of alisol A 24-acetate from the dried tuber of Alisma canaliculatum. Alisol A 24-acetate inhibited RANKL-mediated osteoclast differentiation by downregulating NFATc1, which plays an essential role in osteoclast differentiation. Furthermore, it inhibited the expression of DC-STAMP and cathepsin K, which are related to cell-cell fusion of osteoclasts and bone resorption, respectively. Therefore, alisol A 24-acetate could be developed as a new structural scaffold for inhibitors of osteoclast differentiation in order to develop new drugs against osteoporosis.